PENGOLAHAN SAMPAH RUMAH TANGGA MENJADI PRODUK KREATIF DAN BERNILAI EKONOMI DI MANGGALA, ANTANG - Anshariah, Anshariah; Sukmawati, Sukmawati; Basalamah, Muhammad Syafi’I A (MAJU : Indonesian Journal of Community Empowerment, 2025)
His community service program was implemented to address the increasing problem of household waste in Manggala, Antang, which contributes to environmental pollution and decreases community well-being. The program aims to reduce waste volume while enhancing community skills in recycling and transforming waste into creative products with economic value. The methods used include education, practical training, and mentoring using a participatory approach. Local residents who are partners are trained to process organic waste into compost and utilize used cooking oil waste into soap that can increase economic value.The products created demonstrate potential market value, contributing to additional household income. Furthermore, the program fostered local creativity, strengthened environmental awareness, and opened opportunities for small-scale businesses. Overall, this initiative contributes not only to environmental sustainability but also to economic empowerment for the community in Manggala, Antang.